Exploring instructional differences and school performance in high-poverty elementary schools. Issue 1 (2nd January 2018) - Hirn, Regina G.; Hollo, Alexandra; Scott, Terrance M.
ABSTRACT: In the United States, federal funding under Title 1 is provided to schools to improve academic achievement for disadvantaged students. Many students attending schools eligible for Title 1 funding are from families in poverty and at risk for negative outcomes. Identifying instructional factors that mitigate this risk must be a priority for teachers and school administrators, especially in high-poverty schools. Active instruction that increases student engagement has long been identified as a critical element of academic achievement. The purpose of this study was to explore teachers' use of teacher behaviors representing active instruction (specifically, provision of opportunities to respond [OTR] and feedback) in 22 high- and low-performing Title 1 elementary schools. Results of multilevel modeling indicated that although school-level variance was limited, teachers varied in rates of group OTR and negative feedback across schools: teachers in high performing schools delivered higher rates of group OTR and lower rates of negative feedback. Implications for research and practice are discussed.